Renyi Entropy Derivation for a Modified Skewed Student-t Distribution - Nkombou, M. B. W.; David, I. J.; Okeke, E. N. (Mikailalsys Journal of Mathematics and Statistics, 2025)
This paper derives the Renyi entropy for a modified Skew Student-t distribution (SStD). The skew Student-t distribution was modified using DUS transformation technique. The final expression of the Renyi entropy was derived using the probability density function of the transformed (SStD).